Analisis Potensi Kebangkrutan Dengan Model Altman Z-Score Pada PT. Matahari Department Store Tbk - Alisa Misran; Sitti Hajerah Hasyim; Samirah Dunakhir (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the potential bankruptcy of PT Matahari Department Store Tbk for the 2021–2024 period using the Revised Altman Z-Score model. Bankruptcy analysis is measured through financial ratios in the Altman model. The results show that the financial condition of PT Matahari Department Store Tbk during the 2021–2024 period fluctuated. The company's working capital value showed an unstable condition with several years in a negative position. Retained earnings and EBIT also showed a significant decline in 2023 before increasing again in 2024. Analysis based on the Revised Altman Z-Score model shows that the company's Z-score tends to move between the gray area and potential distress categories, reflecting the presence of financial pressure that needs to be anticipated. This is influenced by declining profitability, high liabilities, changes in retail market conditions, and increasing industry competition